Conceptualizing dual use: A multidimensional approach - Martin Hähnel (Research Ethics Review)
The problem of dual use is characterized by a wide range of activities or types of research and technology utilization. In this article, I explore the phenomenon of dual use in several steps to make it accessible for ethical inquiries: first, I examine the phenomenon in more detail; is it a genuine property of technologies and methods, a fundamental problem for research ethics, or a specific precondition for trade-off situations? Second, I show that various factors contribute to a certain good becoming a real dual use good. Third, I propose to develop a three-dimensional classification and evaluation system for dual use risks.